To multiply the polynomial expressions \( (x + 2)(x - 4) \), we can use the distributive property (also known as the FOIL method for binomials):
-
First: Multiply the first terms:
\( x \cdot x = x^2 \) -
Outer: Multiply the outer terms:
\( x \cdot (-4) = -4x \) -
Inner: Multiply the inner terms:
\( 2 \cdot x = 2x \) -
Last: Multiply the last terms:
\( 2 \cdot (-4) = -8 \)
Now, combine all the results:
\[
x^2 - 4x + 2x - 8
\]
Combine the like terms (\(-4x + 2x\)):
\[
x^2 - 2x - 8
\]
Thus, the final result is:
\[
x^2 - 2x - 8
\]
In summary, the coefficients are:
\(? = 1\),
\(? = -2\),
\(? = -8\)
So the polynomial expression is \( x^2 - 2x - 8 \).